(untitled) (Research, Society and Development, 2021)
School Psychology, as an intervention area, research and support for the training of students for a field of work, has the Professional Orientation as one of its traditional themes of interest. With that in mind, this study aims to analyze the perception and performance of four school psychologists on the process of professional choice of high school students in two private schools in São Luís - MA. This is a qualitative research, in which the procedure involved was to interview psychologists and the instrument used to gather the information was the application of three semi-open questionnaires. The results show that the interviewees perceive the importance of Professional Orientation as an integral discipline of formal education and the relevance of their performance as mediators in the subjective and social processes of their students. It is reiterated that other studies are necessary to increase knowledge about the possible contributions of the school psychologist in relation to the role of the school in the trajectory of the subjects that in the future will be serving the society through their professions.